2018
DOI: 10.4314/tjpr.v17i5.28
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-molecular-weight heparin and unfractionated heparin on traumatic disseminated intravascular coagulation

et al.

Abstract: Purpose: To explore the effects of unfractionated heparin (UFH) and low-molecular-weight heparin (LMWH) on traumatic disseminated intravascular coagulation (DIC). Methods: A total of 77 cases of severe trauma (APACHE II score: 5-10) with DIC were collected and randomly assigned to one of three groups: LMWH treatment-26 cases were subcutaneously injected with LMWH (75-150 units/kg/d); UFH treatment-25 cases were subcutaneously injected with UFH (100-250 units/kg/d); control-26 cases supplemented with blood coag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Patients were diagnosed by the ISTH criteria and divided into three groups, treated by heparin ( n = 25), LMWH ( n = 26), and “coagulation factors only” as a control group ( n = 26). Results showed a significant difference in mortality rate in the control group in comparison with the two treatment groups and no substantial difference was observed between heparin and LMWH groups (57.7% control, 19.2% LMWH, and 24% heparin) [ 13 ]. In another clinical trial, the effect of heparin was analyzed in the treatment of newborn infants with respiratory distress syndrome and DIC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients were diagnosed by the ISTH criteria and divided into three groups, treated by heparin ( n = 25), LMWH ( n = 26), and “coagulation factors only” as a control group ( n = 26). Results showed a significant difference in mortality rate in the control group in comparison with the two treatment groups and no substantial difference was observed between heparin and LMWH groups (57.7% control, 19.2% LMWH, and 24% heparin) [ 13 ]. In another clinical trial, the effect of heparin was analyzed in the treatment of newborn infants with respiratory distress syndrome and DIC.…”
Section: Resultsmentioning
confidence: 99%
“…In two RCT studies, the effect of LMWH was investigated alone or with heparin in separate groups. Interestingly, both of them demonstrated that heparin and its preparations have a significant effect on the reduction of mortality rate in DIC patients [ 9 , 13 ]. Sakuragawa et al reported a 7.8% mortality rate in heparin group and no mortality was observed in the LMWH group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, APTT is used to measure the inhibition efficacy of both intrinsic and common coagulation pathways, and TT is used to measure the clot formation time for fibrinogen being converted into fibrin by thrombin . In this study, HLSA acted as a heparinized material because of the heparin-mimetic groups.…”
Section: Resultsmentioning
confidence: 99%